Monster cats. 2 - Pandania (Seven Seas Entertainment, 2024)
"Spend more time with our old monster cat friends and meet some new ones, too. What's it like to have a cat that's also a gnome, a banshee, a gorgon or a kelpie? Enjoy watching life with these devilish supernatural pets go on in strange but oddly familiar ways."--Back cover.